EVALUASI NIAT BERKELANJUTAN WAJIB PAJAK TERHADAP LAYANAN EâFILLING - , Fitri Candra Wardana, Sony Warsono Dr., MAFIS., Ak. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research develops for predicting the implementation of electronic tax filling services using IS continuance intention model by Bhattacherjee (2001) which modified added Delone and McLean (2003) variables: system quality, information quality, and service quality. Bhattacherjee (2001) suggest that userâs continuance intention is determined by their satisfaction with IS use and perceive usefulness. It is an empirical study using purposive sampling and snowball sampling judgments in data collection methods. The subject of this study was the taxpayer who has tried or have been using eâfilling system in DI Yogyakarta and Jakarta. Analysis of data using SmartPLS 2.0. The result of this research show that: there is a positive and significant influence of user satisfaction on continuance intention